Using ICF to Describe Problems With Functioning in Everyday Life for Children Who Completed Treatment for Brain Tumor: An Analysis Based on Professionals' Documentation - Ann-Christin Björklund; Ann-Christin Björklund; Mats Granlund; Sheila Judge Santacroce; Karin Enskär; Stefan Carlstein; Maria Björk (Frontiers Media S.A., 2021)
Background: Children treated for brain tumors often experience persistent problems affecting their activity performance and participation in everyday life, especially in school. Linking these problems to the International Classification of Functioning, Disability and Health (ICF) classification system can be described as affecting body function, activity performance, and/or participation. Services involved in the everyday life of the child have different focus and goals when meeting the child in context, which advantage the use of ICF to overcome this impediment to follow-up and provide comprehensive support for children who have completed treatment for a brain tumor.Aim: The aim of the study was to use the ICF classification system to describe how professionals in healthcare, habilitation, and school document problems with everyday life functioning at body, activity, and participation levels for children who completed treatment for a brain tumor.Materials and Methods: A retrospective review of records from healthcare, habilitation, and school concerning nine children completed treatment for brain tumor was implemented. Identified problems in everyday life were linked to ICF codes. Descriptive statistics of ICF-linked code frequency supplemented by network visualization diagrams viewing the co-occurrence between codes within the body, activity participation, and environmental components were performed.Results: Most documented problems were found in healthcare records, whereas the documentation in habilitation and school was sparse. The frequently occurring codes, independent of record source, were linked to the body function component, and ICF-linked problems in habilitation and school were salient in the activity and participation component. To gain a holistic picture of relations between ICF codes and problems, network visualization diagrams were used to illustrate clusters of problems.Conclusion: Code prevalence likely reflects where healthcare professionals and educators focus their attention when meeting the needs of children treated for a brain tumor in context. To maximize the comprehensive view of functioning and participation of children in everyday life, the full range of difficulties regarding body impairments, activity limitations, and participation restrictions must be identified and linked to each other in patterns of co-occurrence, which the ICF facilitate. However, ICF provides no guidance on how to identify networks of problems within the body, activity, and participation. Identifying such networks is important for building comprehensive interventions for children.